THE ROLE AND ANALYSIS OF THE STOCK MARKET IN ATTRACTING INVESTMENTS (Conferencea, 2023)
The need to strengthen the protection of the rights of investors and minority shareholders, improve the payment and collection of dividends was stressed. In addition, the task was given to develop corporate governance, transition to international financial reporting and international auditing standards.